2011
DOI: 10.1111/j.1467-7652.2011.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale transcriptome analysis in chickpea (Cicer arietinum L.), an orphan legume crop of the semi‐arid tropics of Asia and Africa

Abstract: Chickpea (Cicer arietinum L.) is an important legume crop in the semi-arid regions of Asia and Africa. Gains in crop productivity have been low however, particularly because of biotic and abiotic stresses. To help enhance crop productivity using molecular breeding techniques, next generation sequencing technologies such as Roche/454 and Illumina/Solexa were used to determine the sequence of most gene transcripts and to identify drought-responsive genes and gene-based molecular markers. A total of 103 215 tenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
215
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 250 publications
(232 citation statements)
references
References 51 publications
(100 reference statements)
13
215
4
Order By: Relevance
“…Using a combination of ab initio modeling, and homology-based searches with gene sets from six plant species, including legumes, and the CaTA transcript sequences 8 , we predicted a nonredundant set of 28,269 gene models, with average transcript and coding sequence sizes of 3,055 bp and 1,166 bp, respectively (Supplementary Table 7). Most of these genes have homology with gene models in TrEMBL 9 (89.58%) and Interpro 10 (70.03%) databases.…”
Section: Genome Assembly and Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a combination of ab initio modeling, and homology-based searches with gene sets from six plant species, including legumes, and the CaTA transcript sequences 8 , we predicted a nonredundant set of 28,269 gene models, with average transcript and coding sequence sizes of 3,055 bp and 1,166 bp, respectively (Supplementary Table 7). Most of these genes have homology with gene models in TrEMBL 9 (89.58%) and Interpro 10 (70.03%) databases.…”
Section: Genome Assembly and Annotationmentioning
confidence: 99%
“…The chickpea genome assembly contained 81,845 SSRs, of which 48,298 SSRs were suitable for PCR primer design for use as genetic markers (Supplementary Tables 16 and 17). SNP discovery using 1,073 million Illumina transcript reads and 15 million 454-sequencer transcript reads generated in an earlier study 8 from four desi genotypes of chickpea (ICC 506, ICC 1882, ICC 4958, ICCC 37) and one accession (PI 489777) of the progenitor species C. reticulatum Table 18 and Supplementary Fig. 7).…”
Section: Polymorphisms For Chickpea Breeding and Geneticsmentioning
confidence: 99%
“…However, in another comprehensive study, after aligning 37 million Illumina short sequence tags generated from drought-challenged root tissues of the same genotypes as used in the transcriptome assembly, Hiremath et al (2011) identified 2974 TUSs with significant expression changes, 2823 of which could be associated with gene ontology annotations. Furthermore, the expression patterns of many genes suggested that their role in various pathways of secondary metabolism.…”
Section: Transcriptome Sequencing In Chickpeamentioning
confidence: 99%
“…Among legume crop species, several versions of transcriptome assemblies were generated by different research groups (Table 2). For instance, in the case of chickpea, several transcriptome assemblies based on different sequencing platforms have been developed (Garg et al, 2011a;2011b;Hiremath et al, 2011). These assemblies together with unpublished data from the University of Saskatchewan have been used for defining a comprehensive trasncriptome assembly (Lam et al, 2010) comprising of 46,369 contigs with an average N50 of 1,726 bp (Kudapa et al, 2014).…”
Section: Glyma07g05410/ Glyma16g01980mentioning
confidence: 99%
“…Flowering time/maturation Homology based (Kim et al, 2012) GmDGAT2C/ GmDGAR1B Seed yield Homology based (Eskandari et al, 2013) conserved orthologous sequence (COS) and intron spanning region (ISR) markers Hiremath et al, 2011;Jhanwar et al, 2012;Kudapa et al, 2012). Using the Roche 454-FLX platform, a transcriptome assembly in M. truncatula was generated with a total of 184,599 contigs (Cheung et al, 2006) and this assembly was found to contain 610 SSRs.…”
Section: Glyma07g05410/ Glyma16g01980mentioning
confidence: 99%